CEO cognitive trust, governmental support and marketing innovation: empirical evidence from Chinese small, medium and micro enterprises - Jiafeng Gu (Journal of Knowledge Management, 2022)
Purpose This study aims to verify the influence of chief executive officer (CEO) cognitive trust and governmental support on marketing innovation. Additionally, it evaluated the influence of CEO cognitive trust on the marketing innovation of small, medium and micro enterprises (SMMEs). Design/methodology/approach The authors empirically assessed the impact of CEO cognitive trust on SMME marketing innovation. Furthermore, the authors examined the mediating effect of governmental support on this relationship. The authors then studied a sample of 1,770 SMMEs in China by applying partial least squares structural equation modeling. Findings The authors found that CEO cognitive trust was negatively associated with marketing innovation. Moreover, governmental support has a competitive mediating effect on this relationship. Thus, while governmental support is urgently needed to enhance the marketing innovation of SMMEs, CEO cognitive trust negatively impacts this relationship. Research limitations/implications This study empirically establishes the importance of CEO cognitive trust and governmental support as antecedents in SMME marketing innovation. This contributes to the knowledge base of the management field, adding to important streams in the wider business literature, such as marketing studies, leadership management, strategic management and innovation. While the model is parsimonious, the relationships it highlights are robust and can be generalized to other contexts. Practical implications Managers must not only have high levels of trust and authority but must also embody these characteristics rationally. Simultaneously, managers must actively establish a trusting relationship with the government, thereby improving their company’s ability to integrate government policy information while also actively seeking governmental support. These measures are helpful in enhancing the marketing innovation capabilities of SMMEs. Social implications SMMEs occupy an important position in all countries’ economies and their vitality directly determines the strength of the economy. Formulating reasonable marketing strategies will help enhance market competitiveness and promote the rapid development of SMMEs. Originality/value The literature on marketing innovation has paid little attention to CEO cognitive trust, while CEOs’ cognitive characteristics are an increasingly relevant antecedent in SMME marketing innovation. This study analyzed CEO cognitive trust as a possible antecedent of marketing innovation activities in SMMEs, with this influence path being evaluated. This study extends the current knowledge in this field by considering the effects of CEO cognitive trust on marketing innovation.